2014
DOI: 10.3389/fimmu.2014.00600
|View full text |Cite
|
Sign up to set email alerts
|

Progression to AIDS in SIV-Infected Rhesus Macaques is Associated with Distinct KIR and MHC class I Polymorphisms and NK Cell Dysfunction

Abstract: Killer cell immunoglobulin-like receptors (KIR) regulate the activity of natural killer (NK) cells and have been shown to be associated with susceptibility to a number of human infectious diseases. Here, we analyzed NK cell function and genetic associations in a cohort of 52 rhesus macaques experimentally infected with SIVmac and subsequently stratified into high viral load (HVL) and low viral load (LVL) plasma viral loads at set point. This stratification coincided with fast (HVL) and slow (LVL) disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 57 publications
(70 reference statements)
1
38
0
Order By: Relevance
“…A growing amount of evidence suggesting the role of particular activating Mamu-KIR3DS alleles in influencing plasma viral loads in SIV-infected rhesus macaques has surfaced from associative studies (Albrect et al 2014; Chaichompoo et al 2010). Similarly, the copy number of Mamu-KIR3DS genes is speculated to influence peak viral loads following SIVmac251 infection in Indian rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%
“…A growing amount of evidence suggesting the role of particular activating Mamu-KIR3DS alleles in influencing plasma viral loads in SIV-infected rhesus macaques has surfaced from associative studies (Albrect et al 2014; Chaichompoo et al 2010). Similarly, the copy number of Mamu-KIR3DS genes is speculated to influence peak viral loads following SIVmac251 infection in Indian rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%
“…identified individual KIR genes with either a protective or a detrimental effect in SIV‐infected rhesus macaques. KIR3DL02 , KIR3DSW08 and most probably also KIR3DS01 are associated with slow disease progression, longer survival times, higher numbers of blood NK cells, and higher lytic capability of NK cells . In contrast, KIR3DS02 , KIR3DL10 and KIR3DL05 were more frequently found in animals with fast disease progression, shorter survival times, lower numbers of blood NK cells, and decreased lytic capability of NK cells .…”
Section: The Kir and Mhc Class I Gene Families Of Macaquesmentioning
confidence: 94%
“…In a further study, this group demonstrated high KIR2DL4 copy numbers to be associated with a better preservation of CD4 + T cells and an increased interferon‐ γ production of stimulated CD56 − CD16 − NK cells in SIV‐infected rhesus macaques . Albrecht et al . identified individual KIR genes with either a protective or a detrimental effect in SIV‐infected rhesus macaques.…”
Section: The Kir and Mhc Class I Gene Families Of Macaquesmentioning
confidence: 95%
See 1 more Smart Citation
“…Specific interactions between KIRs of primates and MHC class I ligands are being identified and monoclonal antibodies against primate KIR proteins are being generated 220, 221. These advances are enabling phenotypic characterization of KIR expression on NK cells and T‐cell subsets in primates and investigation of KIR‐MHC biology in primate models of infectious disease 222, 223, 224…”
Section: Kir Model Systemsmentioning
confidence: 99%